2016
DOI: 10.1016/j.sjbs.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Batch culture and repeated-batch culture of Cunninghamella bainieri 2A1 for lipid production as a comparative study

Abstract: This research was performed based on a comparative study on fungal lipid production by a locally isolated strain Cunninghamella bainieri 2A1 in batch culture and repeated-batch culture using a nitrogen-limited medium. Lipid production in the batch culture was conducted to study the effect of different agitation rates on the simultaneous consumption of ammonium tartrate and glucose sources. Lipid production in the repeated-batch culture was studied by considering the effect of harvesting time and harvesting vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Results in this study exhibited that increasing the time of drain and fill from 12 h to 48 h led to enhance butanol production, productivity and yield. This is in agreement with a study reported by Dashti and Abdeshahian (2016) who found that increasing the time from 12 h to 48 h created a progressive increase in the production of lipid which indicated the positive influence of increasing the time on the metabolic activity of Cunninghamella bainieri 2A1 in the fermentation for lipid production. Table 2 summarized the butanol production, yield and productivities for butanol and total ABE at different times of DFT.…”
Section: Comparison Of Batch and Repeated Batch Fermentation For Butasupporting
confidence: 93%
See 1 more Smart Citation
“…Results in this study exhibited that increasing the time of drain and fill from 12 h to 48 h led to enhance butanol production, productivity and yield. This is in agreement with a study reported by Dashti and Abdeshahian (2016) who found that increasing the time from 12 h to 48 h created a progressive increase in the production of lipid which indicated the positive influence of increasing the time on the metabolic activity of Cunninghamella bainieri 2A1 in the fermentation for lipid production. Table 2 summarized the butanol production, yield and productivities for butanol and total ABE at different times of DFT.…”
Section: Comparison Of Batch and Repeated Batch Fermentation For Butasupporting
confidence: 93%
“…The reduction was higher in 50% DFv compared to 25% DFv because of the increase in the volume of replacing medium which recorded as 1.12 at run 2 and 0.67 at the end of run 5. Dashti and Abdeshahian (2016) had stated that the highest level of the biomass concentration had been obtained during the first cycle of the repeated batch culture, which indicated that an increase in the number of repeated batch cycles had an adverse influence on biomass concentration and microbial cell growth.…”
Section: Fermentation In Repeated-batch Culturementioning
confidence: 99%
“…One way to overcome this would be in situ product removal by calcium salt precipitation as shown for U. maydis [48] and U. vetiveriae [44] or by reactive extraction methods [49]. Alternatively, a continuous or semi-continuous process with cell recycling can help to overcome product toxicity as well, by extending the productive time of the biomass [50].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…This cultivation system allows for better dynamics and higher efficiency of the biosynthesis process by extending the effective production phase in comparison to traditional batch culture [7]. The RBC was already successfully used for lipid, ethanol and erythritol production [79].…”
Section: Introductionmentioning
confidence: 99%